Āthār-i Fatḥallāh Khān-i Shaybānī. Volume 1 : Jild-i avval Dīwān-i ashʿār, Fatḥ u ẓafar - Shaybānī, Fatḥallāh Khān, (Miras Maktoob, ISBN: 9789004365452., 2019)
Fatḥallāh Khān Shaybānī (d. 1308/1891) was a major poet of the Qajar era who belonged to the so-called 'return' movement, which wanted to break free from the Sabk-i Hindī or 'Indian style' in poetry, that was popular in Iran since Safavid times. Shaybānī was born in a suburb of Kashan around 1241/1825. Having completed his education there and thanks to his father's connections, he became a companion of the future Nāṣir al-Dīn Shāh Qājār (r. 1264-1313/1848-96). However, due to courtly intrigues he was soon expelled, an expulsion which would last a full 35 years before relations were restored. In that period he served in various official capacities, lastly as the governor of Mashhad. Between assigments, he lived in the countryside near Natanz for around 25 years. Shaybānī's work, here published in full, is characterized by an aversion of undue embellishments, his choice of subjects, his criticism of politics and society, and his concrete suggestions for change. 2 vols; volume 1.